2004
DOI: 10.1109/tbme.2003.821054
|View full text |Cite
|
Sign up to set email alerts
|

Multifrequency Microwave Thermograph for Biomedical Applications

Abstract: This paper presents problems related to thermal radiation of human bodies in microwave range with respect to diagnosis of breast carcinoma. A mathematical model of thermal radiation transfer through tissues is introduced and methods of measurement of temperature, depth and size of a heat source, by means of multifrequency microwave thermograph are described. Theoretical considerations are supplemented by presentation of experimental results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…However, the classifier was profiled to applications for this particular task and required a ground truth group, which is not possible in all cases of thermal image analysis . There are also other known methods of image analysis presented in publications or fully automatic ones presented in . But still they are profiled to specific tasks and expected results.…”
Section: Discussionmentioning
confidence: 99%
“…However, the classifier was profiled to applications for this particular task and required a ground truth group, which is not possible in all cases of thermal image analysis . There are also other known methods of image analysis presented in publications or fully automatic ones presented in . But still they are profiled to specific tasks and expected results.…”
Section: Discussionmentioning
confidence: 99%
“…The detection of temperature differences using ONCOSCAN was utilized as a substitute for breast biopsies for diagnosis.The readings obtained from the 130 subjects that were scanned indicated that the system had high predictive power when coupled with mammography. In 2004, Stec et al [ 36 ] developed a system to measure and model deep-seated temperature distributions in biological tissues by means of multi-frequency microwave thermography. The mapping of temperature variations as a function of depth obtained from this model was consistent with the findings of known physical models.…”
Section: Microwave Breast Imagingmentioning
confidence: 99%
“…Creation possibility of the single-frequency radiothermometer constructed according to the R. H. Dicke scheme which is inexpensive, small-sized, stable, highly sensitive device and consists of available microwave components is investigated in work [32]. Results of research in the field of creation of multi-channel and multi-frequency radiometers are presented in [30,31,[33][34][35][36][37][38]. Registration of information is carried out by a multi-channel radiometer with antennas tuned to different frequencies, or a single-channel multi-frequency radiometer.…”
Section: Main Partmentioning
confidence: 99%